Algebraic Description of Monadic Second Order Logic - Kahtan H. Alzubaidy; Nabila M. Bennour (International Journal of Mathematics And its Applications, 2025)
A direct algebraic description of monadic second order logic in terms of Boolean algebras of unary and binary relations are given by extending the method of [1].